That Uncertain Feeling - How Consumption Responds to Economic Uncertainty in Norway - Jørgen Gudmundsson; Gisle James Natvik (Norges Bank, 2012)
Economic theory predicts that higher uncertainty motivates households to consume less. In this paper we empirically assess how household consumption in Norway responds to variation in economic uncertainty. We consider alternative measures of uncertainty, volatility indexes from financial markets and the frequency with which economic uncertainty is mentioned in the Norwegian press. We find that a one standard deviation rise in our preferred measure of uncertainty is followed by a statistically significant fall in overall consumption reaching a maximum of about 0.6% after one year. For durable consumption the fall is larger, reaching a maximum of 2% after one year. These responses are consistent with precautionary savings affecting all consumption components, and additional wait-and-see effects for durable consumption.
hdl:11250/2507179
Keywords: 330; economic uncertainty; consumption